Large-Scale Beard Extraction Enhances the Cosmetic Results of Scalp Hair Restoration in Advanced Androgenetic Alopecia in East Asian Men: A Retrospective Study - De-Cong Zhu; Ye He; Zhe-Xiang Fan; Jin Wang; Qian Qu; Zhi-Qi Hu; Yong Miao (Adis, Springer Healthcare, 2019)
Abstract Introduction Beard hair serves as an important additional donor supply to support hair transplantation in hirsute patients with extensive alopecia and lacking sufficient occipital hair. However, the efficacy and safety of large-scale beard hair extraction have not been studied extensively in the East Asian population. Methods Data obtained from hirsute patients with extensive alopecia who underwent hair transplantation between March 2017 and December 2018 at Nanfang Hospital were analyzed. Occipital and beard hair were evaluated separately during the pre-, intra-, and post-operative periods. Individual beard hair follicular units (FUs) were harvested under tumescence using a hollow punch with an outer diameter of 0.8-0.9 mm. Follow-up examinations were scheduled at 3-5 days, 1 month, and 9 months postoperatively to check for complications, determine the survival rate of mixed, transplanted FU grafts, and assess patient satisfaction. Data were collected and analyzed statistically. Results A total of 36 hirsute, male patients with advanced androgenetic alopecia (AGA) (Norwood-Hamilton V-VI) were included in this study. The density of the occipital and beard areas was 78.6 ± 4.6 and 48.4 ± 9.3 FU, respectively. It took 3.1 ± 0.9 h to harvest 3135 ± 863 FUs from the occipital area and 2.1 ± 0.6 h to harvest 2352 ± 599 FUs from the beard area. The transection rate for occipital FUs and beard FUs was 3.7 ± 0.4 and 3.9 ± 0.2%, respectively. Completion of the operation took approximately 10.0 ± 0.9 h, and no serious complications were reported 5 days after the procedure. An FU survival rate of 95.7 ± 1.6% was observed at 9 months after transplantation, with no visible hypopigmented scars observed in the bare areas. All patients were satisfied with the resulting cosmetic appearance. Conclusion Large-scale beard extraction, when combined with occipital hair extraction, is a safe and effective treatment to enhance the cosmetic appearance of East Asian men with advanced AGA.